2020
DOI: 10.1186/s13099-020-00360-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of Arcobacter species in human stool samples derived from out- and inpatients: the prospective German Arcobacter prevalence study Arcopath

Abstract: Background: Arcobacter species, particularly A. butzleri, but also A. cryaerophilus constitute emerging pathogens causing gastroenteritis in humans. However, isolation of Arcobacter may often fail during routine diagnostic procedures due to the lack of standard protocols. Furthermore, defined breakpoints for the interpretation of antimicrobial susceptibilities of Arcobacter are missing. Hence, reliable epidemiological data of human Arcobacter infections are scarce and lacking for Germany. We therefore performe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…were detected in 1.3% (89/6774) and 1.7% (5/298) of clinical stool samples respectively [ 14 , 31 ]. Other studies, conducted in Turkey, Germany, India, Chile and Belgium, reported different prevalence rates ranging from 0.3 to 4% [ 17 19 , 32 , 33 ]. After identification using multiplex PCR and verification by rpoB sequencing all isolates were classified as A. butzleri .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were detected in 1.3% (89/6774) and 1.7% (5/298) of clinical stool samples respectively [ 14 , 31 ]. Other studies, conducted in Turkey, Germany, India, Chile and Belgium, reported different prevalence rates ranging from 0.3 to 4% [ 17 19 , 32 , 33 ]. After identification using multiplex PCR and verification by rpoB sequencing all isolates were classified as A. butzleri .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the reported prevalence of Arcobacter among humans range from 0.3 to 4% [ 17 , 18 ]. Recent studies have shown that Arcobacter was the second and fourth most common bacterial pathogen isolated from human stool samples in Germany and Belgium, respectively [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further to the lack of scientific justification for the Pérez-Cataluña et al [5] proposals, we feel there is a risk to the wider scientific community that a reclassification of certain Arcobacter sensu lato species poses. Many Arcobacter species are widely recognized as emerging human [3, [23][24][25][26][27][28][29][30] and animal [31][32][33][34], pathogens, including recognition by an international body as agents of foodborne illness [4]. The revised nomenclature therefore presents a potential source of confusion for clinicians, veterinarians and diagnosticians, with corresponding important implications for accurate epidemiological monitoring and reporting.…”
mentioning
confidence: 99%
“…Other strains isolated from different environmental, clinical, animal, and agri-food sources were provided by the Ottawa Research and Development Centre at Agriculture and Agri-Food Canada (Ottawa, ON, Canada) and Arcobacter Research Lab at Freie Universität Berlin (Berlin, Germany). All bacterial strains were identified to species level using multiplex PCR assays, followed by sequencing of PCR amplicons as described in the previous studies (3,(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…I n recent years, Arcobacter has been considered an emerging food-and waterborne pathogen and potential zoonotic agent (1). This genus currently comprises 29 recognized species isolated from environmental, animal, agri-food, and human sources (2,3). Among these, the most frequently reported species is A. butzleri, which is classified as a serious hazard to human health (4).…”
mentioning
confidence: 99%